Strategies for Stabilization of Zn Anodes for Aqueous Zn-Based Batteries: A Mini Review - Mo, Funian; He, Ning; Chen, Lina; Li, Mengrui; Yu, Suzhu; Zhang, Jiaolong; Wang, Wenhui; Wei, Jun (Frontiers in Chemistry, 2022)
In recent years, thanks to the investigation of the in-depth mechanism, novel cathode material exploitation, and electrolyte optimization, the electrochemical performance of rechargeable Zn-based batteries (RZBs) has been significantly improved. Nevertheless, there are still some persistent challenges locating the instability of the Zn anodes that hinder the commercialization and industrialization of RZBs, especially the obstinate dendrites and hydrogen evolution reaction (HER) on Zn anodes, which will dramatically compromise the cycle stability and Coulombic efficiency. Therefore, various strategies with fundamental design principles focusing on the suppression of dendrite and the HER have been carefully summarized and categorized in this review, which are critically dissected according to the intrinsic mechanisms. Finally, pertinent insights into the challenges and perspectives on the future development of Zn anodes are also emphasized, expecting to supply potential research directions to promote the practical applications of RZBs.